KUR’ÂN TEDRİSATINDA HARF TALİMİNİN ÖNEMİ VE USÛLÜ - (:unkn) unknown (My University, 2021)
İnsanlar için sağlıklı hücreler, binalar için sağlam temeller ne kadar önemliyse, nitelikli birKur’ân tilaveti için de harfler o derece önemlidir. Zira harf telaffuzu problemli olduğunda hemtilavet hem de -namazın rükünlerinden olması hasebiyle- namazdaki kıraat gayr-ı sahiholacaktır. Bu nedenle harf talimi, Kur’ân tedrisatının en önemli ve hatta en önceliklimeselelerindendir. Kur’ân eğitimcisinin, öğrencilerinin kıraatinin sahih olabilmesi için özenleüzerinde durması gereken bir mevzu olan harf talimi, alan bilgisi (uzmanlık) gerektirdiği kadarpedagojik ve metodolojik yaklaşım (usûl) becerisini de gerektiren bir özelliğe sahiptir. Zira aksibir tutum, öğrencilerin hem Kur’ân tilavetlerini hem de Kur’ân’a olan muhabbetlerini olumsuzbir şekilde etkileyecektir. Böyle bir olumsuz etki ise onların Kur’ân’a ömürlük bir kitap olarakdeğil, derslik (sezonluk) bir kitap gibi yaklaşmalarına neden olacaktır. Bu makalede eğitimcilere,nitelikli bir Kur’ân tilavetinin yapı taşlarından olan harf talimi hususunda, ifrat ve tefritsavrulmasına kapılmadan mutedil, pedagojik ve metodolojik bir tedrisatın nasıl icraedilebileceğine dair pratik öneriler sunulmaya çalışılacaktır

Arabic letters are significantfor a qualified Qur’ān recitation just as the importance of healthy cells for human-beings and solid bases for buildings. Therefore, the prerequisite for an accurate Qur’ān recitation is to know the names, articulation, characteristics and pronunciation of letters and apply them correctly. Even if a person has a complete theoretical tajwīd knowledge, having a problematic pronunciation willmake his recitation (tilawat) incorrect as well as his qirāʾāt in the prayer, since the qirāʾāt is one of the pillars (rukn) of the prayer. For this reason, a letter pronunciation practice is one of the most important and even the primary issue of Quran teaching. The pronunciation practice, which is the matter that the Quran educators must overemphasize to make their pupils’ recitation accurate, requires field knowledge (expertise) as well as the skills of pedagogical and methodological approaches (usul). In case the mentioned requirements are not fulfilled, the student’s Quran recitation and their attachment to Quran will be affected in a negative way. Such a negative effect will cause them to approach the Qur'an not as a lifetime book, but as aseasonal coursebook. In this article, it is aimed to offer practical suggestions to Quran educators on how to apply a mild, pedagogical and methodological approaches about pronunciation practice which is one of the building blocks of Quran teaching.
THE IMPORTANCE OF LETTER PRONUNCIATION TRAINING AND ITS APPLICATION METHODS IN TEACHING QURĀN RECITATION